2008
DOI: 10.3174/ajnr.a0959
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR Spectroscopy in the Evaluation of Cerebral Metabolism in Patients with Fibromyalgia: Comparison with Healthy Controls and Correlation with Symptom Severity

Abstract: BACKGROUND AND PURPOSE:Widespread pain sensitivity in patients with fibromyalgia (FM) suggests a central nervous system (CNS)-processing problem. Therefore, it is conceivable that metabolic alterations exist in pain-processing brain regions of people with FM compared with healthy controls (HC) and that such metabolic data could correlate with clinical symptoms. The purpose of this study was to test these hypotheses using proton MR spectroscopy ( 1 H-MR spectroscopy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 35 publications
(33 reference statements)
1
38
0
1
Order By: Relevance
“…Although the results of these studies are not homogeneous, [21][22][23][24][25][26][27] because of the different MRS protocols, magnetic fields used, and areas of study, in 4 of these, alterations of the glutamatergic system were detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results of these studies are not homogeneous, [21][22][23][24][25][26][27] because of the different MRS protocols, magnetic fields used, and areas of study, in 4 of these, alterations of the glutamatergic system were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some MRS studies [21][22][23][24][25][26][27] have demonstrated alteration of cerebral metabolites in patients with FM, and though the results are not homogeneous, they strengthen the hypothesis of a neural dysfunction secondary to the pain processing.…”
mentioning
confidence: 94%
“…Recent studies have shown that specific stimuli such as pain or anxiety may markedly influence spectroscopic conditions in the brain metabolically [25,26]. Furthermore, MRS is successfully used in various addictive disorders to elucidate their pathophysiology and withdrawal [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…These modifications seem to be caused by what has come to be called "sensitisation": i.e. a permanent state of neuronal hyperexcitability involving all of the peripheral and central structures of the nociceptive system (18)(19)(20)(21)(22)(23). It has only recently been postulated by some researchers that sensitisation of the nociceptive system plays a major role in determining the intensity and chronicisation of the pain accompanying other rheumatic diseases such as OA and rheumatoid arthritis (24)(25)(26).…”
mentioning
confidence: 99%